2007
DOI: 10.1016/j.radphyschem.2006.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Pulse radiolysis studies of the reactions of bromine atoms and dimethyl sulfoxide–bromine atom complexes with alcohols

Abstract: Dimethylsulfoxide (DMSO) _ Br complexes were generated by pulse radiolysis of DMSO/bromomethane mixtures and the formation mechanism and spectral characteristics of the formed complexes were investigated in detail. The rate constant for the reaction of bromine atoms with DMSO and the extinction coefficient of the complex were obtained to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Sumiyoshi et al observed a similar transient feature in a pulsed-radiolysis study of DMSO and CBrCl 3 mixtures, and they assigned this band at 450 nm to the absorption of a Br • −DMSO complex. 28 Thus, it appears that the stronger interaction between the Br atom and DMSO (a polar solvent) compared to that with CCl 4 (a nonpolar solvent) and the small number density of CHBr 3 relative to that of DMSO favors the formation of the Br • −DMSO complex over that of the CHBr 3 −Br • complex and iso-CHBr 2 −Br • isomer. Figure 3 shows the results of electronic transient absorption measurements for a solution of Br 2 in CH 3 OH following 400 nm excitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sumiyoshi et al observed a similar transient feature in a pulsed-radiolysis study of DMSO and CBrCl 3 mixtures, and they assigned this band at 450 nm to the absorption of a Br • −DMSO complex. 28 Thus, it appears that the stronger interaction between the Br atom and DMSO (a polar solvent) compared to that with CCl 4 (a nonpolar solvent) and the small number density of CHBr 3 relative to that of DMSO favors the formation of the Br • −DMSO complex over that of the CHBr 3 −Br • complex and iso-CHBr 2 −Br • isomer. Figure 3 shows the results of electronic transient absorption measurements for a solution of Br 2 in CH 3 OH following 400 nm excitation.…”
Section: Resultsmentioning
confidence: 99%
“…Our inability to detect HBr is perhaps not surprising. On the basis of the extinction coefficient of the Br • −DMSO complex at the absorption maximum (430 nm) 28 and the IR absorption cross section of HBr in the gas phase, 35 along with the assumption that the 1 mOD offset in the difference signal is entirely due to the loss of the Br • −DMSO complex through a hydrogen-abstraction reaction, we estimate a signal of 17 μOD for transient absorption by HBr. This signal is comparable to our current noise level, making detection of the HBr product using time-resolved IR detection unlikely.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with Cl atom complexes, less is known regarding complexes involving Br atoms. Neta and co-workers used pulsed radiolysis to study the complexes of bromine atoms with various halocarbons and reported spectra of Br atom complexes with DMSO, benzene, and various halons including CH 2 Br 2 , C 2 H 5 Br, CHBr 3 , and CBr 4 . Subsequent studies from our group and others have shown that isohalons are primary photoproducts in many of these systems. For example, recent ultrafast studies of CH 2 Br 2 and CHBr 3 photolysis in solution show prompt formation of the isospecies, which decay over longer time scales to produce a radical pair, with subsequent formation of a Br···solvent complex. In related work, Barbara and co-workers used ultrafast spectroscopy to probe the short-time electron-transfer dynamics in Br atom complexes with benzene and other arenes. , Initial excitation of the Br···C 6 H 6 complex led to electron transfer and the formation of a benzene cation radical and bromide anion.…”
Section: Introductionmentioning
confidence: 99%